Non-syndromic Unilateral Congenital Aural Atresia with Agenesis of Right Mandibular Condyle: A Clinical Report - Bhandari, Ranju; Dali, Mamta; Koirala, Bandana; Birajee, Gajendra (Journal of Nepalese Association of Pediatric Dentistry, 2023)
Ear and mandible share common embryologic origin. Any disturbance in these structures during developmental process may result in disorders such as aplasia or agenesis of ear along with Temporomandibular Joint (TMJ). This can result in facial asymmetry and malocclusion. The resulting malocclusion is best managed surgically at appropriate age to address the facial, skeletal and dental problems but till then a harmonious occlusion is important for sound function and esthetics. This case presents a comprehensive management of dental problems in a patient with unilateral congenital aural atresia with agenesis of TMJ till a definitive treatment is achieved. A 5-year-old male patient diagnosed with congenital aural atresia with agenesis of right TMJ was referred to the Department of Pedodontics and Preventive Dentistry for dental management. After thorough examination and investigation, comprehensive dental management was done to provide ample function, occlusion and esthetics.